La actividad del comercio en Pereira y Dosquebradas. Desarrollo empresarial y construcción de capital social (2019)
This article analyzes the trade in Pereira and Dosquebradas from the perspectiveof Business Development and the influence of the economic activity evolutionon local companies. The results show that companies' strategic decisions arerelated to business development and are translated into social capitalconstruction through administrative and human talent processes. In the text,technological trajectories of companies and employees are specified as also thepractices of human talent and the contribution of this activity to human andsocial capital. It is concluded that businesses are located in Pereira andDosquebradas by the size of the market they have access, and the ease ofcommunication with their customers and suppliers. The companies havetechnological trajectories based on available technology, entrepreneur andemployee's certificate knowledge, and processes certification. Its experience is atthe local, regional and national market. The functions of human talent are carriedout by the administrative departments, and social capital is built throughdifferent mechanisms especially in the employment relationship